Physico-Chemical Characterization of Synthetic Hemozoin Crystal (2022)
ABSTRACT: Plasmodium is a parasite that is transmitted to man by the bite of a mosquito of the Anopheles genus that causes malaria In one of the stages of the life cycle of the parasite in the human body, the plasmodium degrades hemoglobin and forms a crystal called hemozoin, as the main protection mechanism For this reason, a complete understanding of the formation mechanisms and the physical chemical characteristics exhibited by this crystal are very important to understand, to control and to detect the malaria disease 1 4 Additionally, this crystal is also the target of several antimalarial drugs An approach for this type of research is to manufacture in the laboratory, under diverse and controlled conditions and in the presence of various drugs, the synthetic analogue of hemozoin, which is called the β hematin crystal We present the kinetic studies, in aqueous medium, of conversion of hemin to β hematin both in pure form and in the presence of chloroquine, a commonly used antimalarial drug